Simplified Order Conditions of Some Canonical Difference Schemes (Journal of Computational Mathematics, 1995)
The main purpose of this paper is to develop and simplify the general conditions for an $s$-stage explicit canonical difference scheme of $q$-th order, while the simplified order conditions for canonical RKN methods which are applied to a special kind of second order ordinary differential equations are also obtained here.